1992
DOI: 10.1139/v92-210
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium constants and heats of formation of methyl esters and N,N-dimethyl amides of substituted benzoic acids

Abstract: .Heats of methanolysis and dimethylaminolysis of substituted benzoyl chlorides (4-X-C6H4-COC1, X = H, CH,, 0CH3, C1, NO,) have been measured, as have the heats of hydrolysis of the esters, permitting the calculation of the heats of formation of the benzoyl chlorides (4-X-C6H4-COCl, X, DHf: CH30, -80. 29 of transfer from methanol to water and from gas to water were determined for the esters and amides. Free energies of formation in aqueous solution were calculated for the acids, esters and amides, making use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…On the other hand, for esters where OR is attached to an sp2 hybridized carbon the free energy change is almost totally insensitive to electron withdrawal. For R = CF,, CH,, pCH,O-C6H4, C6H5, pN0,-C6H4, AG = +1.65 (20), +1.70 (21), +1.17 (22), +1.26 (22), +1.2 1 (22) (all for reaction in water, where the standard state of water is the pure liquid at unit activity). There does appear to be an effect on changing from an aliphatic to an aromatic acyl substituent, but within each series the effect of drastic change in substituents is very small.…”
Section: Jp ~U T H R I E~mentioning
confidence: 99%
“…On the other hand, for esters where OR is attached to an sp2 hybridized carbon the free energy change is almost totally insensitive to electron withdrawal. For R = CF,, CH,, pCH,O-C6H4, C6H5, pN0,-C6H4, AG = +1.65 (20), +1.70 (21), +1.17 (22), +1.26 (22), +1.2 1 (22) (all for reaction in water, where the standard state of water is the pure liquid at unit activity). There does appear to be an effect on changing from an aliphatic to an aromatic acyl substituent, but within each series the effect of drastic change in substituents is very small.…”
Section: Jp ~U T H R I E~mentioning
confidence: 99%
“…This is in line with the experimentally measured equilibrium constant for the reaction of N , N -dimethylbenzamide 7b and methanol (entry 2), in which the reverse reaction is thermodynamically favored (see Supplementary Information for further discussion). 16 Encouraged by the unique ability of Ni to catalyze the activation of strong aryl –heteroatom bonds, 17 , 18 , 19 particularly those in phenol-, 19 aniline-, 20 , 21 , 22 and phthalimide derivatives, 23 we also calculated the activation energies for acyl C–N bond oxidative addition of each amide substrate using Ni catalysis. The calculated barriers using the commercially available N -heterocyclic carbene (NHC) ligand SIPr (entries 1–8) reveal that the oxidative addition barriers are reasonable in most cases.…”
mentioning
confidence: 99%
“…Almeida et al (and Guthrie et al) have reported the molar standard enthalpy of formation for M4MB in the crystalline phase as −(523.8 ± 2.3) kJ·mol –1 (and as −(520.91 ± 1.63) kJ·mol –1 ). As one can observe, our result, −(527.7 ± 2.7) kJ·mol –1 , agrees with Almeida et al’s value, and the difference is within the experimental uncertainties.…”
Section: Resultsmentioning
confidence: 99%